Determinan Persepsi Kualitas Laporan Keuangan Satuan Kerja Kementrian Negara/ Lembaga di Semarang - Priyono Priyono; Siti Mutmainah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The opinion of the Financial Audit Board on the Financial Reporting of the Ministry of State / Institutions (Laporan Keuangan Kementrian Negara/Lembaga, LKKL) has a positive trend every year, but the summary of the results of the semester examination (IHPS) 2 of 2020 still contains 1956 examination findings related to the implementation of internal control system (sistem pengendalian internal, SPI) and compliance with regulations in the applicable Law. This research uses agency theory which aims to analyze and obtain empirical evidence about determinant of qualitity of LKKL perception. Independent variables in this study are compliance with regulations, human resource competencies, compliance with SPI and utilization of information technology, while the financial report quality as a dependent variable. The population in this study is the entire work unit of the Ministry of State / Institutions in the working area of the Semarang State Treasury Service Office utilizing purposive sampling techniques. The research data used primary data from the questionnaire. The sample in this study amounted to 141 responses, utilizing the Structural Equation Model-Partial Least Square (SEM-PLS) analysis technique. The data processing tool used for this research test is WarpPLS